The Effect of Return on Investment, Debt to Equity Ratio, and Earning Per Share on Stock Price - Sri Irawati Mukhtar; Saprudin; Ubedillah (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2022)
This study was conducted to examine the factors that affect the stock price of manufacturing companies in the goods and consumption industry sector on the Indonesia Stock Exchange, such as Return On Investment (ROI), Debt To Equity Ratio (DER), and Earning Per Share (EPS). The population in this study amounted to 34 companies. The sample selection method in this study used purposive sampling, so that there were five companies as samples in this study. Data obtained through www.idx.co.id. This study uses panel data which is a combination of time series and cross section. The data analysis technique used was descriptive statistical analysis and panel data regression analysis using the software eviuws 9. The results showed partially that ROI 0.0001 < 0.005 had a positive and significant effect on stock prices. DER 0.0060 < 0.005 has a positive and significant effect on stock prices, EPS 0.3776 > 0.05 has a negative and insignificant effect on stock prices and the results show simultaneously the ROI, DER, and EPS values ​​0.000000 < 0.05 jointly affect stock prices in manufacturing companies in the goods and consumption sector for the 2016-2020 period. Keywords: Return On Investment, Debt To Equity Ratio, Earning Per Share, Stock Price